A case of severe Ebstein’s anomaly with incompetent pulmonary valve - Özkutlu, Süheyla; Ceviz, Naci; Ayabakan, Canan; Akçören, Zuhal (The Turkish Journal of Pediatrics, 2002)
A case of Ebstein’s anomaly with functional pulmonary atresia diagnosed in utero is presented. The diagnosis was confirmed by postnatal echocardiographic, angiographic, and postmortem pathologic findings. On echocardiography the septal leaflet of the tricuspid valve was displaced towards the right ventricular apex. The tricuspid valve was moderately regurgitant and the arterial duct was patent. Continuous wave or color Doppler revealed serious reduction in forward flow from right ventricle through the pulmonary arteries; however, massive pulmonary regurgitation was observed. Pulmonary circulation was dependent on the ductal flow due to functional pulmonary atresia. Angiography revealed the massively enlarged right atrium, the absence of forward flow through the tricuspid valve, transfer of contrast material through the atrial septal defect to the left atrium, and the retrograde inflow of the pulmonary arteries from the aorta via the patent arterial duct. Ebstein’s anomaly accompanied by functional pulmonary atresia is very rare. The fetal and neonatal presentation of this anomaly is associated with poor outcome.